Case Report: Clinical manifestations and treatment of two Chinese patients with FINCA syndrome carrying a novel variant of NHLRC2 - Liu, Yuemei; Wang, Hongling; Tang, Yu; Zhang, Lei; Su, Yanyan; Wang, Yanqion; Xu, Shasha; Mei, Shiyue; Jia, Chunyang; Shen, Yuelin; Tang, Xiaolei (Frontiers in Pediatrics, 2024)
Fibrosis, neurodegeneration, and cerebral angiomatosis (FINCA) syndrome is an autosomal recessive inherited disease caused by mutations in the NHLRC2 gene. This case report describes two Chinese siblings with FINCA syndrome carrying a novel frameshift variant c.1610dupT (p.L537Ffs*17) of NHLRC2 gene. They shared similar symptoms of interstitial lung disease (ILD) and neurodegeneration with early onset in infancy and similar chest CT characterized by bilateral ground-glass opacities and consolidations. The elder brother died of infantile respiratory failure, while in the younger brother, respiratory symptoms improved together with chest CT and krebs von den Lungen-6 (KL-6) level after long-term systemic glucocorticoid therapy, indicating that anti-inflammatory treatment may be beneficial in the treatment of ILD caused by FINCA syndrome.